2014
DOI: 10.1371/journal.pone.0105727
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Killer Toxin-Like Candidacidal Ab6 Antibodies Elicited through the Manipulation of the Idiotypic Cascade

Abstract: A mouse anti-anti-anti-idiotypic (Id) IgM monoclonal antibody (mAb K20, Ab4), functionally mimicking a Wyckerhamomyces anomalus (Pichia anomala) killer toxin (KT) characterized by fungicidal activity against yeasts presenting specific cell wall receptors (KTR) mainly constituted by β-1,3-glucan, was produced from animals presenting anti-KT Abs (Ab3) following immunization with a rat IgM anti-Id KT-like mAb (mAb K10, Ab2). MAb K10 was produced by immunization with a KT-neutralizing mAb (mAb KT4, Ab1) bearing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Hydrolysis and fractionation techniques used routinely to determine the polysaccharide content of the sugar of interest have demonstrated that not even trace amounts of di-, tri-, or tetrasaccharides are observed in pustulan, indicating that the molecule is linear in nature and contains exclusive ␤-1,6 glucan linkages (21). Other researchers have routinely used pustulan to study ␤-1,6 glucan-C-type lectin receptor (CLR) interactions and yeast ␤-1,6 glucan cell wall biology (22)(23)(24)(25)(26).…”
Section: Methodsmentioning
confidence: 99%
“…Hydrolysis and fractionation techniques used routinely to determine the polysaccharide content of the sugar of interest have demonstrated that not even trace amounts of di-, tri-, or tetrasaccharides are observed in pustulan, indicating that the molecule is linear in nature and contains exclusive ␤-1,6 glucan linkages (21). Other researchers have routinely used pustulan to study ␤-1,6 glucan-C-type lectin receptor (CLR) interactions and yeast ␤-1,6 glucan cell wall biology (22)(23)(24)(25)(26).…”
Section: Methodsmentioning
confidence: 99%
“…The so-called “antibiobodies” (antibiotic-like antibodies) showed direct fungicidal effects without the intervention of other factors [ 162 ]. Through the immunization of rats and mice against mAbKT4, other monoclonal antibiobodies were obtained, as well as peptides that occur during the idiotypic cascade (mAb K10 and mAb K20) and single-chain fragments (scFv) [ 163 ]. In particular, from scFv H6.…”
Section: Killer Toxins: From a Competitive Advantage To The Applicmentioning
confidence: 99%
“…These mAbs that specifically reacting with killer toxins (KT) from Pichia anomala and Williopsis mrakii have broad antimicrobial spectrum and demonstrated in vitro similar activity to polymorphonuclear neutrophils against the hyphae and germinated conidia of A. fumigatus and in vivo protected immunocompromised mice with invasive aspergillosis from infection [143]. Similar results were observed against C. albicans in vitro and in vaginal and systemic murine models of candidiasis [144,145].…”
Section: Antibody-based Therapymentioning
confidence: 62%